Public Art Replacement on the Mapocho River: Erasure, Renewal, and a Conflict of Cultural Value in Santiago de Chile. Issue 2 (May 2020) - Morrison, Chandra
On January 18, 2011, the Museo Arte de Luz opened along Santiago's Mapocho River. Developed by artist Catalina Rojas and the Santiago municipal government to mark Chile's 2010 bicentenary, the light-art museum proposed to revitalize the river as a public space by converging heritage, contemporary art, and citizenship. Yet controversy lurked behind the newly gleaming lights: museum preparations included the erasure of several large graffiti murals painted along the canal walls. This article examines how the installation of the Museo Arte de Luz systematically removed graffiti muralism from the Mapocho River, drawing out deeper cultural tensions entangled in this aesthetic dispute. It analyses three interconnected discourses about the museum's desired impact on the river—environmental regeneration, historical restoration, and symbolic recuperation—to illustrate how the erasure corresponds to official narratives of renewal. Ultimately, through its contradictions, this public art replacement raises important questions about public authority and cultural value in Chile.